1998
DOI: 10.1136/hrt.79.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Supravalvar aortic stenosis: unexpected findings at surgery

Abstract: A 51 year old man was referred for investigation of presumed valvar aortic stenosis. A murmur had been noted as a child but he had developed normally and was entirely asymptomatic. He had had two episodes of infective endocarditis successfully treated medically in 1968 and 1977. He was currently on no medication. Annual echocardiography had shown a possible bicuspid aortic valve with a pressure gradient of 30 mm Hg and a hypertrophied left ventricle with good systolic function.Examination revealed a fit man wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Total arch replacement of a right-sided aortic arch and aberrant left subclavian aneurysm has been previously reported. 8 Our operative approach differed, however, as we decided to utilize a bilateral thoracosternotomy that facilitated exposure of the proximal descending aorta and proximal left subclavian artery greatly. Total arch replacement along with proximal descending replacement with left subclavian ligation was integral to the management of this aortic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Total arch replacement of a right-sided aortic arch and aberrant left subclavian aneurysm has been previously reported. 8 Our operative approach differed, however, as we decided to utilize a bilateral thoracosternotomy that facilitated exposure of the proximal descending aorta and proximal left subclavian artery greatly. Total arch replacement along with proximal descending replacement with left subclavian ligation was integral to the management of this aortic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Both appear to be caused by mutations involving the elastin gene on chromosome 7q11.23. Grahame‐Clarke et al 8 reported a case of supravalvular aortic stenosis in an otherwise well 51‐year‐old male diagnosed during cardiac surgery. However, there were no other features of Williams syndrome.…”
Section: Commentmentioning
confidence: 99%